Increased use of scheduled teleconsultations and asynchronous messaging from the portal in primary care - Herrera, Ana G.; Piccioli, Sofía; Ruíz Yanzi, María V.; Luna, Daniel R.; Plazzotta, Fernando; Kopitowski, Karin S.; Grande Ratti, María F. (Revista del Hospital Italiano de Buenos Aires, 2024)
Introduction: During the COVID-19 pandemic there was an unprecedented boom in telemedicine, probably due to the forced adoption of technology under epidemiological restrictions. The present study aimed to compare interaction and communication between general practitioners and patients, before and during the pandemic period, in terms of scheduled outpatient consultations and Patient Portal messages.Materials and methods: Cross-sectional with a consecutive sampling of scheduled televisits and messages, occurred between epidemiological weeks (EW) 10 and 23, of 2019 and 2020 respectively. We included 147 family medicine physicians and a capita of 73427 patients affiliated with the Hospital Italiano de Buenos Aires health plan. Quantitative and qualitative analysis was performed.Results: There was a 70% reduction in face-to-face consultations (from 76375 in 2019 to 23200 in 2020), and a concomitant increase in televisits (from 255 in EW13 to 1089 in EW23). Concurrently, messages increased substantially (from 28601 in 2019 to 84916 in 2020), with an abrupt onset at the beginning of the lockdown, and a decreasing trend over time. Prior to the pandemic, the content was related to electronic orders for complementary studies, outcomes follow-up, chronic medication prescriptions, and/or referrals to specialists. The most frequent domains during the pandemic were epidemiological information needs, such as preventive measures for COVID-19, pneumococcal vaccine, influenza vaccine, cases or suspicions, and swab results, among others.Conclusion: The rise of communication and information technologies during the pandemic allowed continuity of health care despite the physical distance, providing remote access to medical assistance, with greater use and acceptance from users. There were transitory information needs from patients, and the patient-physician relationship in primary care has changed during this digital transformation.
Keywords: remote consultation; teleconsultation; telemedicine; e-accessibility; primary health care; Argentina